Potentials of Tamarindus Indica (Linn) in Jam Production (2012)
This study was conducted to investigate the potential of tamarind fruits in jam production with a view to improving utilization efficiency of the fruits thereby adding value to the tree and encouraging its cultivation and sustainable management. The fruits for the study were collected from Bishop Ajayi Crowther University, in Atiba Local Government Area of Oyo town, Oyo State and Taironi Local Government Area of Kano State, Nigeria. The jam was prepared using variable proportions of pulp and sugar. Chemical and microbial analyses were carried out on the jam. Heavy metal contents were determined and sensory evaluation was carried out. Physical and chemical properties of jams produced from the fruits of the two locations were compared. Data generated was analyzed using students t-test. There is no significant difference (p ≤ 0.05) in the moisture contents of the jams produced from the fruits from both locations. Some essential elements including Zn (0.74mg), Mg (0.68mg), Cd (0.26mg), Mn (0.94mg), Pb (0.55mg), Fe (0.29mg), Cr (0.67mg), and Cu (0.17mg) were contained in the jam. The levels of heavy metals found in the jam are significantly lower than the UN/WHO allowable standard for human consumption while some of the other metals are actually of high nutritional values. There are indications that the jam could keep well at room temperature. Oyo State sample is higher in mineral element than that of Kano State. The ascorbic acid content is low in both Kano and Oyo samples. Pulp and sugar were rated most acceptable by a panel of judges on a nine point hedonic scale. Tamarind possesses great potentials for jam making and is safe for human consumption and well accepted by consumers. Further development of the jam to an industrial status was recommended